(untitled) (Third Sector Social Economic Review, 2023)
From past to present, earthquake disasters experienced in our country together with COVID-19 pandemic have led to series of preventive measures in social and economic terms. At the beginning of these preventive and regulatory measures necessary attention has been taken to ensure education and training activities are not disrupted. While such negative situations caused temporary disruption and suspension of education and training activities in past distance education process, online learning were handled together at time. This study is to examine and evaluate effects of online learning perceptions students studying accounting in light of today’s rapidly advancing educational technologies on their distance education satisfaction. İt was investigated what kind of effects the opinions of students studying the undergraduate level and taking accounting courses at university might have regarding online learning within scope of their perception of distance education satisfaction. Study was analyzed using empirical methods appropriate scales. significant effect of student perceptions accounting education regarding online learning on distance education satisfaction levels (β: 0.163 p<0.05) was determined. It is thought that study will help decision makers in order to increase the quality of education and training activities future and will draw a road map especially for academicians who provide accounting education.